The influence of the SARS-CoV-2 lockdown on patients with inflammatory rheumatic diseases on their adherence to immunomodulatory medication: a cross sectional study over 3 months in Germany. (11th March 2021) - Hasseli, R; Müller-Ladner, U; Keil, F; Broll, M; Dormann, A; Fräbel, C; Hermann, W; Heinmüller, C -J; Hoyer, B F; Löffler, F; Özden, F; Pfeiffer, U; et al.
Abstract: Objectives: To evaluate the influence of the SARS-CoV-2 pandemic on the adherence of patients with inflammatory rheumatic diseases (IRD) to their immunomodulatory medication during the three-month lockdown in Germany. Methods: From 16 th March until 15 th June 2020, IRD patients from private practices and rheumatology departments were asked to answer a questionnaire addressing their behaviour with respect to their immunomodulating therapy. Eight private practices and nine rheumatology departments that included rheumatology primary care centres and university hospitals participated. A total of 4252 questionnaires were collected and evaluated. Results: The majority of patients (54%) were diagnosed with RA, followed by psoriatic arthritis (14%), ankylosing spondylitis (10%), connective tissue diseases (12%) and vasculitides (6%). Most of the patients (84%) reported to continue their immunomodulatory therapy. Termination of therapy was reported by only 3% of the patients. The results were independent from the type of IRD, the respective immunomodulatory therapy and by whom the patients were treated (private practices vs rheumatology departments). Younger patients (<60 years) reported just as often as older patients to discontinue their therapy. Conclusion: The data show that most of the patients continued their therapy in spite of the pandemic. A significant change in behaviour with regard to their immunomodulatory therapy was not observed during the three months of observation. The results support the idea that the immediate release of recommendations of the German Society of Rheumatology were well received, supporting the well-established physician–patient relationship in times of a crisis.